Dimensionamento de fundações diretas em sapatas: Desenvolvimento de software - Alexandre, Fernanda Barbosa (2018)
Due to the great variation in its composition, the soils are considered complex elements and this can cause difficulties in the elaboration of a geotechnical project of foundation. This work aims to show that even trough these difficulties it is possible to automate the dimensioning of foundations by footing through the development of a software in the Visual Basic language, seeking to awaken the engineers and the technical community in general of the importance in improving the technical quality and automation geotechnical projects dealing with surface foundations. The methodology adopted is based on bibliographical research on the subject, in order to acquire the theoretical basis necessary for the development of the program's calculation routine. In the computational algorithm of the same, a semi-empirical method was used to calculate the permissible soil tension, which relates the result of the SPT test with this voltage. After the footing were dimensioned, the elasticity theory and Schmertmann (1978) methods were used, and finally, it was possible to calculate the quantitative and budget of these footings. Subsequently, the software was used in a practical application so that the results provided could be analyzed and discussed. These results showed that the difference between the two values is quite significant, a fact that was already expected, since, according to the bibliographical research, they are used in different situations and depend on the characteristics of the soils.